The central nervous system in childhood chronic kidney disease - Gipson, Debbie S. (Pediatr Nephrol, 2007)
Neurodevelopmental deficits in pediatric and adult survivors of childhood onset chronic kidney disease (CKD) have been documented for many years. This paper reviews the available literature on central nervous system involvement incurred in childhood CKD. The studies reviewed include recent work in neuroimaging, electrophysiology, and neuropsychology, along with commentary on school functioning and long-term outcomes. The paper concludes with suggestions for monitoring the neurodevelopmental status and pursuing appropriate early interventions for children with CKD.